THE EFFECT OF DISASTER PREPAREDNESS TRAINING ON EARTHQUAKE PREPAREDNESS AT SDN MADANI PALU - Sukrang, Sukrang; Hasnidar, Hasnidar; Fauzan, Fauzan (Homes Journal: Hospital Management Studies Journal, 2024)
Central Sulawesi has a high potential for large-scale disasters such as earthquakes, tsunamis, and liquefaction which can lead to severe physical damage and a high death toll. It is estimated that 60–70% of Indonesia's disaster victims are women, children, and the elderly. Due to their lack of independence, children are among the most vulnerable populations affected by natural disasters. As a result, efforts are required to raise kids' awareness of natural disaster preparedness. This research aims to analyze the effect of disaster preparedness training on elementary school children's preparedness for earthquakes. This study applied a quasi-experimental research, particularly the Nonequivalent Control Group Design. In this case, the samples involved are 40 students of SDN Madani Palu. Furthermore, the test used is the Wilcoxon test and the Mann Whitney test with a significance level of p <0.05. The study's findings revealed a Mann Whitney U-Test score of p = 0.314 (p>0.05), indicating that both the treatment and control groups were equally prepared for earthquakes. However, the post-observation data revealed a p value of 0.000 (p <0.05), indicating a significant difference between the treatment and control groups' levels of earthquakes disaster preparedness. This indicates that improving the level of preparedness for earthquakes disasters is a result of providing SDN Madani Palu children with disaster preparedness training that includes lecture, audio-visual, and simulation methods. It can be concluded that there is an effect of disaster preparedness training on the preparedness of elementary school children for earthquake disasters